Comparative analysis of chloroplast genomes in Carica species reveals evolutionary relationships of papaya and the development of efficient molecular markers - Chen, Yajin; Du, Xiaoxi; Pan, Lei; Huang, Qiyuan; Hao, Zhigang (Frontiers in Plant Science, 2025)
Papaya (Carica papaya L.) has a very high economic value, making it one of the “three major tropical herbaceous fruit trees” alongside banana and pineapple. However, it faces major challenges due to limited genetic diversity resulting from monocultures and barriers to interspecific hybridization, which seriously affect yield, quality, and disease resistance. To elucidate phylogenetic relationships among diverse cultivars and facilitate marker-assisted selection in breeding, we sequenced and analyzed the chloroplast genomes of 17 representative papaya cultivars, including commercial cultivars (e.g., ‘Guangmi’ and ‘Tainong’) and agricultural cultivars, by Illumina sequencing technology. The chloroplast genome showed a conserved tetrad-loop structure encoding 131 functional genes, and phylogenetic analyses using maximum likelihood (ML) revealed their evolutionary relationships and resolved two major clades. Whole-chloroplast genome sequence alignment analysis identified hypervariable non-coding regions, enabling the development of three high-resolution molecular markers (trnG–trnR, rbcL–accD, and rpl12–rps19). The three markers effectively distinguished key breeding lines (YZ1 and Tainong), providing a robust toolkit for germplasm innovation and marker-assisted breeding in papaya. This study not only provides a theoretical foundation and technical means for the genetic improvement of papaya but also serves as a reference for research on chloroplast resources in other tropical fruit trees.